Kearifan Lokal sebagai Basis Perilaku Kewirausahaan Pelaku UMKM Etnis Timor di Kota Kupang Nusa Tenggara Timur - Karlos Losiana Banoet; Maya Angelina Seran; Maria Litvina Prada Manek; Gusto Winardi Kare; Ernestus Ikun; Chikita Olmin Maharani Naru; Enike Tje Yustin Dima (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to explore how local wisdom of the Timorese ethnic group serves as a basis for entrepreneurial behavior among MSME actors in Kupang City. The phenomenon examined is the persistence of collective cultural values amid the pressures of urban market modernization faced by Timorese MSME actors. This research employed a qualitative phenomenological approach to capture the meaning and lived experience of informants regarding the internalization of cultural values into their entrepreneurial practices. Data were collected through in-depth semi-structured interviews with six MSME actors of Timorese ethnicity operating in six sub-districts of Kupang City, engaged in diverse business sectors including grocery retail, ikat weaving, livestock farming, traditional culinary, handicrafts, and agricultural produce trading. The findings reveal four dominant themes: local wisdom as social capital, entrepreneurial behavior framed within collective values, negotiation between customary obligations and business rationality, and the non-material meaning of business success. Notably, all informants consistently practiced a coping strategy of providing limited family assistance without recording it as formal business debt when customary obligations conflicted with capital sustainability. This study contributes theoretically by refining the relationship between local wisdom and entrepreneurial behavior as dialectical and institutionalized, rather than simply unidirectional and harmonious. Practically, the findings inform MSME mentorship programs in designing financial literacy modules that accommodate the separation between business funds and social solidarity funds. Future research is recommended to expand the number of informants and research locations to strengthen data triangulation.